High-resolution sampling of beam-driven plasma wakefields - S. Schröder; C. A. Lindstrøm; S. Bohlen; G. Boyle; R. D’Arcy; S. Diederichs; M. J. Garland; P. Gonzalez; A. Knetsch; V. Libov; P. Niknejadi; Kris Põder; et al. (Nature Communications, 2020)
Controlled particle acceleration in plasmas requires precise measurements of the excited wakefield. Here the authors report and demonstrate a high-resolution method to measure the effective longitudinal electric field of a beam-driven plasma-wakefield accelerator.